(untitled) (Práxis Educativa, 2020)
The coronavirus (COVID-19) pandemic poses challenges in all spheres of human life, especially in social policies. In this scenario, we analyzed the conditions for conducting emergency remote education for a 4th grade of Elementary Education student with Autism Spectrum Disorder (ASD). The exploratory study started from the analysis of an experience report, and was anchored in the cultural-historical approach of human development, especially the idea that socio-historical, cultural, and political conditions are a source of psychic activity development. The results show the place of the school in the student’s life and point to this social institution role as a collective space of political and pedagogical resistance and an institution that mediates humanization processes. Keywords: Special Education. Remote education. COVID-19.